Avaliação da qualidade do biodiesel em função da matéria-prima utilizada: óleos residuais de fritura de diferentes tipos e fontes - Morais, Verônica Santos de (2011)
Brazil is known worldwide for its position of 47.2% of renewable energy matrix. However, it occupies the 6th place worldwide in publication of patents on the production of biodiesel, showing the need of research involving this matrix. The use of vegetable oils refined to produce biodiesel has numerous disadvantages, among which are the high cost and competition with the food industry. The reduction of pollution impacts caused by improper disposal of waste frying oils is the main motivation for using this matrix in biodiesel production, besides its low cost. In this study, biodiesel was produced employing four sources of waste frying oils. It was performed Physical Chemistry (ASTM Color Test, Density, Viscosity and Total Acid Value) and elemental (sodium, potassium, magnesium and calcium) analysis of the waste frying oils and of the their biodiesel to assess the influence of the characteristics of raw materials on the quality of biodiesel produced. Although most of biodiesel produced met the quality standards monitored by the supervisory body, it is important to note that the differences between the sources of waste frying oils, grouped in vegetable oils and fats, influence the final quality of biodiesel produced. Using analysis of variance (ANOVA), it was verified that the parameters ASTM color, viscosity, total acid value and sodium content measured in waste frying oils and their biodiesel are affected by matrix type (vegetable oils or fats) whereas the parameters for density, calcium and magnesium content arenot affected by matrix type. Through principal component analysis (PCA) it was verified that kinematic viscosity of the waste frying oil was crucial to distinguish the four different sources used in production of biodiesel. This multivariate analysis alsoallowed us to observe that the density and ASTM color distinguished the characteristics of biodiesel, defining the separation of the biodiesel produced in four groups according to their sources of the waste frying oil. In light of the small number of publications relating to the quality of the biodiesel with its raw material, this work contributed to demonstrate this relationship. The application of these statistical tools to other parameters measured in waste oils and in biodiesel can be useful to select the most relevant parameters in determining the quality of both.